Variational model with nonstandard growth conditions for restoration of satellite optical images using synthetic aperture radar - D’APICE, C.; KOGUT, P.I.; MANZO, R.; UVAROV, M.V. (European journal of applied mathematics, 2023)
In this paper, the problem of restoration of cloud contaminated optical images is studied in the case when we have no information about brightness of such images in the damage region. We propose a new variational approach for exact restoration of optical multi-band images utilising Synthetic Aperture Radar (EOS – Spatial Data Analytics, GIS Software, Satellite Imagery – is a cloud-based platform to derive remote sensing data and analyse satellite imagery for business and science purposes) images of the same regions. We prove existence of solutions, propose an alternating minimisation method for computing them, prove convergence of this method to weak solutions of the original problem and derive optimality conditions.